Implementasi Kebijakan Pemerintah dalam Penataan Parkir Guna Mewudjudkan Tertib Lalu Lintas (Studi Kasus di Kota Labuan Bajo Kabupaten Manggarai Barat) - Bonifasius Fantura; I Ketut Kasta Arya Wijaya; I Nyoman Subamia (Warmadewa Press, 2020)
This research is motivated by awareness and concern for public order, especially in tourist areas. This study aims to determine the policy actions of the West Manggarai Regency Government in managing parking in order to create orderly traffic and to find out the factors that hinder the parking arrangement in order to create orderly traffic in Labuan Bajo City, West Manggarai Regency. This research was designed using a qualitative descriptive method. The techniques used in collecting data are through interviews and documentation. The results show that the government's policy actions in managing parking in the city of Labuan Bajo have not run according to the regulations in the Labuan Bajo city area. Then, there was a mistake between the content of the policy and the implementation in the field. In addition, there is still a lack of awareness from the public to obey traffic regulations, especially parking and a lack of complete facilities where there are 2 areas that are at the center of congestion, namely Jl Soekarno Hatta and Jl. Mirror Stone Market. So this situation makes the people become a habit and low awareness in conducting parking arrangements in the city of Labuan Bajo. Therefore, through this research it is hoped that the Labuan Bajo City Government will increase the parking area in the shopping and market areas so as not to cause congestion. Then, the government is expected to be more assertive in providing guidance to parking attendants in order to comply with applicable regulations.